2011
DOI: 10.5402/2011/365894
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Vitamin B12 Status of Pregnant Women in Nigeria Using Plasma Holotranscobalamin

Abstract: Maternal vitamin B12 deficiency during pregnancy is an independent risk factor for neural tube defects and other neurological problems in infants. We determined the vitamin B12 status of 143 pregnant women in Nigeria representing all trimesters who presented to an antenatal clinic in Jos, Nigeria, using holotranscobalamin II levels (holoTCII), which is a measure of the vitamin B12 that is available for uptake into tissues. The holoTCII concentration ranged from 13 to 128 pmol/L. Using a cutoff of 40 pmol/L, 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Similar challenges can be found in the eastern and south (national territories) areas of the country and may explain the higher prevalence of B 12 deficiently found in those regions compared with more developed areas of the country (Bogota, central, and Atlantic regions) that include large urban centers. Previous studies have found that children living in urban areas and in geographic regions with greater economic and structural development in general had higher serum concentrations than those from rural and poorer areas [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar challenges can be found in the eastern and south (national territories) areas of the country and may explain the higher prevalence of B 12 deficiently found in those regions compared with more developed areas of the country (Bogota, central, and Atlantic regions) that include large urban centers. Previous studies have found that children living in urban areas and in geographic regions with greater economic and structural development in general had higher serum concentrations than those from rural and poorer areas [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of the total vitamin B 12 concentration in plasma is the usual method for assessing vitamin B 12 status. However, neurologic and hematologic symptoms of depletion can occur in individuals with plasma vitamin B 12 concentrations in the lownormal range [22]. Nevertheless, associations between vitamin B 12 marginal depletion and adverse health outcomes in observational studies are concerning and urgently need further evaluation in clinical trials [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, directly comparing these two population groups is inevitably challenging, as values that fall within normal ranges outside of pregnancy may not represent optimization of risk reduction during pregnancy and embryogenesis. It is also important to remember that non-pregnant reference ranges themselves differ between laboratories ( 27 , 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results highlighted a decrease in sB 12 across trimesters 1 through to 3 of pregnancy, in line with findings from previous studies ( 3 , 27 29 ). This could be deemed as a natural consequence of progression in pregnancy and increased demand as it has been previously shown that sB 12 remains constant throughout pregnancy in Nigerian women with adequate B 12 intakes ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, MMA is affected by intestinal bacterial overgrowth and tHcy is elevated by deficiencies of vitamin B6, folate, and riboflavin. Recent investigations show that holoTC (the metabolically active fraction of B12 available to cells) is a more sensitive indicator of vitamin B12 status than the total serum vitamin B12 level or the serum concentration of MMA and plasma tHcys [26][27][28][29][30]. The reference values for non-pregnant women are often applied to assess B12 deficiency in pregnant women.…”
Section: Vitamin B12 Deficiencymentioning
confidence: 99%